2009
DOI: 10.1021/bm801178f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Poly(N-vinyl-pyrrolidone)-block-poly(d,l-lactide) as Coating Agent on the Opsonization, Phagocytosis, and Pharmacokinetics of Biodegradable Nanoparticles

Abstract: The effect of the coating polymer poly(N-vinyl-pyrrolidone) (PVP) on the protein adsorption, phagocytosis, and pharmacokinetics of poly(D,L-lactide)-based nanoparticles was evaluated in vitro and in vivo. Control poly(ethylene glycol) (PEG)-coated nanoparticles were included for comparison. While no difference between PEG-and PVPdecorated nanoparticles in terms of amount of adsorbed protein was evident upon incubation in single protein solutions (BSA, IgG), incubation in serum revealed a protein adsorption pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
94
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(98 citation statements)
references
References 43 publications
3
94
1
Order By: Relevance
“…The protein-NP interaction is studied by incubating NPs in protein solutions for a period of time, either a single protein solution such as BSA, fibronectin and IgG, [11][12][13][14] or biological fluid containing multiple proteins such as serum, 15,16 plasma, cytosol, 17 fetal bovine serum (FBS), 18 fetal calf serum, synovial fluid, and cerebrospinal fluid. 19 Protein-NP complexes are then separated from the protein solution via instrumental analysis.…”
Section: Instrumental Analysis For Evaluating Protein Coronamentioning
confidence: 99%
“…The protein-NP interaction is studied by incubating NPs in protein solutions for a period of time, either a single protein solution such as BSA, fibronectin and IgG, [11][12][13][14] or biological fluid containing multiple proteins such as serum, 15,16 plasma, cytosol, 17 fetal bovine serum (FBS), 18 fetal calf serum, synovial fluid, and cerebrospinal fluid. 19 Protein-NP complexes are then separated from the protein solution via instrumental analysis.…”
Section: Instrumental Analysis For Evaluating Protein Coronamentioning
confidence: 99%
“…11 Recently, it was reported that the capability of PVP to prevent protein adsorption was correlated with its coating and molecule weight. 13,14 It was found that the nanoparticles coated by PVP, with molecular weight of 2,500 and 4,800 Da, were rapidly removed from blood due to complement components and immunoglobulins adsorption. 14 In this report, we loaded UA into poly(N-vinylpyrrolidone)-block-poly (ε-caprolactone) (PVP-b-PCL) nanoparticles and performed physiochemical characterization.…”
mentioning
confidence: 99%
“…13,14 It was found that the nanoparticles coated by PVP, with molecular weight of 2,500 and 4,800 Da, were rapidly removed from blood due to complement components and immunoglobulins adsorption. 14 In this report, we loaded UA into poly(N-vinylpyrrolidone)-block-poly (ε-caprolactone) (PVP-b-PCL) nanoparticles and performed physiochemical characterization. In vitro and in vivo antitumor effects of the UA-loaded PVP-b-PCL nanoparticles (UA-NPs) were evaluated.…”
mentioning
confidence: 99%
“…As an example of biocompatible functionalization, polyethylene glycol (PEG) and poly N-vinyl-2-pyrrolidone (PVP) were exploited to modify nanovectors for gene drug/delivery [17][18][19] , tumor targeting 20,21 A c c e p t e d M a n u s c r i p t and x-ray imaging 22 . For in vivo applications using PEG-gold nanoparticles, all the preparations were based on conventional methods (i.e.sodium citrate or sodium borohydrate reduction) and post-addition of thiolated PEG leading to gold particles usually larger than 20 nm 23 .…”
Section: Introductionmentioning
confidence: 99%